Evaluation of reciprocal F1 crosses of Fayoumi with two exotic chicken breeds 2: additive and non‑additive effects on egg quality traits - Negash, F.; Abegaz, Solomon; Tadesse, Y.; Jembere, T.; Esatu, Wondmeneh; Dessie, Tadelle (Springer, 2023)
The current study evaluates additive and non-additive genetic variances for egg quality traits in six genotypes generated through pure mating and reciprocal crossing of Fayoumi (FM) with Koekoek (KK) and White Leghorn (WL). For each genotype, measurements were taken on 30 eggs randomly sampled at 32, 36, and 40 weeks of age to evaluate both external and internal egg quality parameters. The results revealed significant differences (P < 0.001) among the genotypes in all external quality traits and most internal quality traits, including yolk weight (YW), albumen weight (AW), and yolk height (YH). The results also showed that variations due to purebred effect (PE), general combining ability (GCA), maternal effect (ME), and specific combining ability (SCA) were significant in most traits, which reflects that both additive and non-additive variances are important for the inheritances of the parameters investigated. In most of the traits, the ME and PE were higher in KK and WL, while GCA was higher in KK and FM. The FM x WL had higher SCA than FM x KK. The results suggest the likelihood of genetic improvement in these genotypes through selection and crossbreeding strategies and/or a combination of the two.